DESIGN OF ANDROID-BASED ZAKAT INFORMATION SYSTEM APPLICATION AT BABUL FIRDAUS MOSQUE - Kasmawati; Mustamin, Mustamin; Hasrul, Hasrul (Fakultas Teknik Universitas Negeri Makassar, 2025)
This research aims to make it easier for the community to do zakat and improve the data collection system. The method used is Research and Development (R&D) with a prototype development model, as well as data collection techniques through interviews, observations, and questionnaires. The result of this research is an Android-based zakat information system application intended for admins and people who want to do zakat at the Babul Firdaus Mosque. This application is tested using the ISO 25010 standard with four main aspects: functional suitability, portability, usability, and performance efficiency. Functional suitability testing by the validator lecturer shows that this application is